On-farm Agro-meteorological evaluation of late sown wheat (Triticum aestivum) under irrigated agro-ecosystem of Upper Indo-Gangetic Plains - SHAMIM, M; PANWAR, A S; RAVISANKAR, N; JAT, PC; PRUSTY, A K; SINGH, M P; KASHYAP, POONAM; VERMA, NISHA; DATT, SHIV; ANSARI, M A; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2021)
In Indo-Gangetic Plains (IGP, ~18 mha geographical area), wheat (Triticum aestivum L.) is a predominant cropgrown in rabi. Improving the productivity of wheat in a rice-based farming system through a suitable cultivar inIGP is necessary to evaluate under the agro-ecological condition of IGP of India. A farmer’s participatory fieldexperiment was studied at three villages Saunta, Sathedi and Bhangela situated in Khatauli block of Muzaffarnagar(Uttar Pradesh) under two crop environments (low rainfall and high temperature, LRHT and heavy rainfall and lowtemperature, HRLT) with four wheat varieties during rabi of 2017–18 and 2018–19. In this study we have evaluatedthe productivity in isolation as well as in combination of prevailing weather scenario (2017–18 and 2018–19) underirrigated agro-ecosystems of Western Plain Zone of Uttar Pradesh. Interaction studied between crop environmentsand varieties indicated that PBW-550 and PBW 658 registered higher grain yield of 5514 and 5475 kg/ha, respectivelythan farmers practice (PBW-226, 4659 kg/ha) and DBW-90 (4647 kg/ha) in LRHT. However, under HRLT, PBW-658performed better (5326 kg/ha) over other cultivars. Mean grain yield of all four cultivars were recorded significantlyhigher under LRHT with 5074 kg/ha compared to HRLT where mean grain yield was 4710 kg/ha. A highly significant(P=0.01) negative association was found between grain yield and monthly rainfall (except December month) andcumulative rainfall of the crop season (-0.322**). Prevailing mean monthly air temperature during grain filling tomaturity phenophase was found to be positively associated with grain yield (r = -0.322*).